Protection of human dignity in the context of cyber warfare: the status quo of international law regulating the use of force - Luchagula, Hellen; Bakta, Seraphina M. (Journal of Contemporary African Legal Studies, 2024)
A research paper submitted to the Journal of Contemporary African Legal Studies: Volume 1, Issue 2, 2023, pp. 89-106